2017
DOI: 10.1097/acm.0000000000001912
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Analysis of Professional Conflicts in Health Care Teams: Insight for Future Training

Abstract: Understanding conflicts between health care professionals involves several interrelated dimensions, such as sources, consequences, and responses to conflict. There is a need to strengthen health care professionals' ability to identify and respond to conflict and to further develop conflict management programs for clinical supervisors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 35 publications
0
28
0
10
Order By: Relevance
“…The overall aim of the project was to explore how health care professionals experienced conflicts and to describe conflict characteristics. This led to the publication of a framework to understand conflicts as cyclical ‘wicked problems’ and to provide suggestions for training in conflict management . As we were collecting and analysing the data, we observed that some participants strongly identified with social groups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall aim of the project was to explore how health care professionals experienced conflicts and to describe conflict characteristics. This led to the publication of a framework to understand conflicts as cyclical ‘wicked problems’ and to provide suggestions for training in conflict management . As we were collecting and analysing the data, we observed that some participants strongly identified with social groups.…”
Section: Methodsmentioning
confidence: 99%
“…Although task conflicts can be productive in clarifying opinions and finding innovative solutions, conflicts are usually perceived negatively. Studies have suggested that conflicts can lead to poor communication, suboptimal patient care and further tensions if left unaddressed . One of the key reasons for communication failure is difficulties members of the team have in raising their concerns with their hierarchy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of primary care providers poses a major problem to the US healthcare system [29][30][31][32]. Healthcare is associated with a strenuous workload and due to clinical staffing level constraints and budgetary pressures healthcare systems have engineered new strategies to make sure the delivery of care [33][34].…”
Section: Doctors and Pasmentioning
confidence: 99%
“…The introduction of PA workforce into maxillofacial outpatient settings has allowed the surgeons to focus more on patient care whilst increasing the number of patients seen in the outpatient settings with better outcomes and this has translated into improved productivity and profits [44]. The primary reason for the difference in opinion between physicians and PAs has been related to differences in patient care and communication issues [29].…”
Section: Doctors and Pasmentioning
confidence: 99%